Implementation of Web-Based Maktabah Shamilah Application in Thematic Interpretation Research - Lubis, Ibrahim Siddiq; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
The use of information technology in the Islamic field is increasingly developing into various aspects of academic life. One of the real implementations of these developments is the maktabah shamilah application. This application is a digital platform that provides access to various sources of tafsir practically. This study aims to investigate the implementation of the web-based Maktabah Samilah Website in thematic tafsir research. This research uses a qualitative method with descriptive analysis. We have used descriptive analysis through exploring the use of the web-based Maktabah Shamilah application to study thematic tafsir. This study found that the web-based Maktabah Samilah application presents a variety of interpretations quickly and practically and makes it easy for users to obtain a variety of interpretations that have been included in the application. This research is expected to provide detailed insights accompanied by visualization of how to utilize the web-based Maktabah Shamilah in researching thematic tafsir studies.